Assessing the impact of a patient education programme on pressure ulcer prevention in patients with spinal cord injuries. Issue 4 (November 2019) - Robineau, S.; Nicolas, B.; Mathieu, L.; Duruflé, A.; Leblong, E.; Fraudet, B.; Gélis, A.; Gallien, P.
Abstract: Objectives: There is currently a low level of evidence for the impact of patient education on the management of patients with chronic neurological disease at risk of developing pressure ulcers. The objective of this study was to assess the impact of a patient education programme on pressure ulcer prevention in patients with chronic spinal cord injuries. Materials and methods: This study included adult patients with any spinal cord injury, regardless of the cause. Participants attended 2 group workshops focusing on pressure ulcer prevention. Various clinical data were gathered during an initial individual interview and at 3, 6 and 12 months, along with rating scale values from the Hospital Anxiety and Depression Scale, Rosenberg self-esteem scale, Schwarzer self-efficacy scale, a quality of life scale (SF-36) and the revised Skin Management Needs Assessment Checklist (Revised SMnac), which was used as the primary endpoint. Results: Twenty patients were included in the study. The mean patient age was 52 years (SD: 9, 8). Sixteen patients had traumatic spinal cord injuries, with a median injury duration of 234 months (IQR: 123–407). Seventy-five percent had had a pressure ulcer in the twelve months prior to the study. Patient education was shown to have a significant impact on skin management ability, with a highly significant increase in the overall revised SMnac score at 3 months. These results were stable over time, from 6 to 12 months. Six patients developed a pressure ulcer during the study (30%). Conclusion: This study supports the hypothesis that a therapeutic educational program conducted at the chronic phase in spinal cord injured individuals has an impact. Highlights: Patients education was shown to have a significant impact on skin management ability, with a highly significant increase in the overall score at 3 months. This study supports the hypothesis that a therapeutic educational program conducted at the chronic phase in spinal cord injured individuals has an impact.